Клієнтоорієнтований підхід до управління веб-проектами - Алєксєєва, Катерина (Видавництво Львівської політехніки, 2013)
The paper discusses the use of customer-centric approach in development and further maintenance of commercial web-projects. The concepts of client and customer-centricity were defined. Possible way of implementation of customercentric approach was described.
Keywords: клієнтоорієнтованість; управління проектами; клієнт; цільова аудиторія